Ricky Ricotta's mighty robot vs. the mutant mosquitoes from Mercury - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Ricky Ricotta's mighty robot series, 2014)
A mouse named Ricky Ricotta and his giant flying robot attempt to save the world from an invasion of massive mutant mosquitoes from Mercury.